PARTICIPATION OF SUPERFICIAL MUSCULO-APONEUROTIC SYSTEM OF THE FACE IN CORRECT DENTAL OCCLUSION - Marius V. Hinganu; Delia Hinganu; Laurian L. Frîncu (Romanian Society of Oral Rehabilitation, 2013)
Facial SMAS is a unitary structure with both general and particular characters, specific for each topographic region, with alternating of tension zones with others more lax. Authors have proposed to follow, through various methods of exploration, anatomy of musculofascial formations and of terminal branches of facial nerve with perioral topography. Dissection of anatomical pieces, intraoperatory and imagistic studies, bring arguments about the role of support provided to superficials layers of the face, affecting indirectly, but decisively achievement of correct occlusion and therefor mastication. Dermal insertion of perioral superficial facial muscles allow lip mobilizing and their zygomatic and mandibular attachments provides symetric occlusion in all 3 axes of space. Supporting force vectors of SMAS in zygomatic and temporal attachments act as levers for proper contraction of masticatory muscles.